Four-week of local electromyostimulaiton training on fingerboard increases the isokinetic wrist strength and endurance - Dicle Aras; Selçuk Gül; Fırat Akça; Mehmet Gülü; Özkan Güler; Cemil C. Bıldırcın; Erşan Arslan; Güney Çetinkaya (Physical Education of Students)
Background and Study Aim: Electromyostimulaiton (EMS) has been used for both physical therapy and strength improvements for a few decades. This study aimed to investigate the effects of a four-week local-EMS training performed on a fingerboard (FT) in wrist strength and endurance.